A theory driven identificationand ranking of critical success factors of logistics digitalisation - Ng, Jie Qin (Nanyang Technological University, 2022)
Digitalisation refers to the use of digital technologies to manage business process and models and boost business efficiency and effectiveness. In recent years, digitalisation has been rising in terms of importance in the logistics sector. Thus, examining the critical success of digitalisation adoption (DA) is crucial. Although previous research mainly focused on the trends and implications of DA, practical research on how it can be implemented was still lacking. Therefore, this study aims to fill the gap by identifying and ranking the CSFs of DA using a theory focused approach. The CSFs were developed using the theoretical lenses of four organisational theories. Mainly, stakeholder theory, resource-based view theory, innovation diffusion theory and contingency (fit) theory. Further 19 sub-criteria were identified to operationalise the CSFs. A survey questionnaire was created and was administrated by 21 logistics companies in Singapore. Next, the data was further analysed using the fuzzy analytic hierarchy process. The results of the survey show that the CSFs of DA in descending order of importance are (1) inter-firm resource, (2) contingency theory, (3) stakeholder’s expectations and (4) innovation diffusion theory. Moreover, the results of the study showed that among the sub-criteria of DA, the most important ones are primarily linked to tangible and intangible internal resources of a logistics firm. In addition, logistics DA can be improved through understanding the external environmental conditions and addressing the needs of stakeholders.